Efektivitas Teknik Oral dan Teknik Modelling terhadap Keberhasilan Toilet Training pada Toddler. - Kartika, Umy (Jurusan Keperawatan FIKES UNSOED, 2016)
Toilet training is needed by children to control urination and defecation. The failure of toilet training can be caused by inaccuracy teaching children. The techniques used in conducting toilet training are oral technique and modeling technique. This research was to examine the effectiveness of oral technique and modeling technique for a successful toilet training for the toddler. This study used quasi-experiment with two group pre and post-test static design. The total sample of 30 toddlers at Desa Pamijen Kecamatan Baturraden was invited into the study and was divided into two group. The hypotheses were tested by paired t-test. Results showed age range from Ã‚Â 2.1 to 2.6 years old. The parent education was mostlyÃ‚Â senior high school (40%). The oral technique achievement was 33.33 %, while the modeling was 80%. There is a significant difference between the effectiveness of oral technique and modeling technique for successful toilet training as indicated by the disparity between increasing score average of two techniques. Ã‚Â The increasing toileting ability average (0.4933) and t=14.929 (p=0.000) the modeling technique is bigger than the increasing toileting ability average (0.2000) and t=3.873 (p=0,002) oral technique. It concludes that modeling technique is more effective than the oral technique for the successful toilet training for toddler.